Evaluation of micro-abrasion-corrosion on SiO2-TiO2-ZrO2 coatings synthesized by the sol-gel method (2016)
The medical science and the engineering, work to improve the materials used in the manufacture of joint implants, since they have a direct impact on the quality of people life. The surgical interventions are increasing worldwide with a high probability of a second or even a third intervention. Around these circumstances, it was evaluated the behaviour against microabrasion-corrosion phenomena on SiO2 TiO2 ZrO2 coatings, synthesized by the sol-gel method with concentration of the Si/Ti/Zr precursors: 10/70/20 and 10/20/70. The coatings were deposited on AISI 316 LVM stainless steel substrates. The morphological characterization of the wear was made by AFM techniques. It was observed that the coatings with higher levels of titanium have a good response to the phenomena of microabrasion-corrosion.